IMPLEMENTATION OF GREEN MARKETING STRATEGIES IN DEPOK MUSLIM CULINARY MSMEs - Tati Handayani; Sufyati HS; Suharyati; Ahmad Ruslan; Rizka Yusrina (Jurnal Mebis, 2024)
This research discusses the implementation of green marketing strategies in Muslim culinary MSMEs in Depok. The problem identified is the lack of awareness and implementation of environmentally friendly practices in the MSME culinary business which has an impact on environmental sustainability and the attraction of consumers who care about the environment. Green marketing is measured by the factors of green product, green price, green place, and green promotion.The purpose of this study is to analyze the factors of green product, green price, green place, and green promotion that can influence Muslim culinary MSMEs in the Depok area. This type of research with a quantitative descriptive research approach with primary data sources and data collection techniques by distributing questionnaires to culinary MSME players who live in Depok City. Data analysis using factor analysis. The results showed that in the green marketing factors that influence Muslim culinary MSMEs in Depok, a total of four factors were created: factors 1, 2, 3, and 4. Green product, green price, green place, and green promotion tools make up each of these factors. There are only 2 factors that are considered to represent the four factors formed, namely factor 1 and factor 2.